Examining the Influence of Jessica’s Law on Reported Forcible Rape: A Time-Series Analysis - Dierenfeldt, Rick (Criminal justice policy review, 2017)
Since the 1990s, several measures intended to deter sexual offending have been instituted by state governments. A recent example is Jessica’s Law. First adopted in Florida, variations of Jessica’s Law have since been enacted by the majority of states. The impact of this legislation on forcible rape remains unexplored. Using a general deterrence framework, we apply Autoregressive Integrated Moving Average (ARIMA) modeling to monthly Uniform Crime Report (UCR) aggregations of reported forcible rape from 2000 to 2011 in states requiring lifetime electronic monitoring of convicted sex offenders as a condition of Jessica’s Law. Results indicate a null relationship between Jessica’s Law and reported forcible rape. Policy implications related to the efficacy of sex offender legislation and alternatives for reducing sexual offending are discussed.